Next-generation leadership development in family businesses: the critical roles of shared vision and family climate - Miller, Stephen P. (Frontiers in Psychology, 2014)
The multigenerational survival rate for family-owned businesses is not good. Lack of a shared vision for the family enterprise and weak next-generation leadership are often cited as two of the leading reasons for the failure of family firms to successfully transition from one generation of family ownership to the next. The climate of the business-owning family has also been suggested as important to the performance of the family enterprise. Despite these commonly held tenets, there is a lack of rigorous quantitative research that explores the relationships among these three factors. To address this gap, a quantitative study of 100 next-generation family firm leaders and 350 family and non-family leaders and employees with whom they work was conducted. The results demonstrate that a shared vision for the family business has a strong effect on the leadership effectiveness of next-generation family leaders and a moderate effect on the degree to which they are positively engaged with their work. The findings also show that two dimensions of family climate significantly influence the likelihood that a shared vision for the family firm has been created. Open communication in the family is positively related to the presence of a shared vision for the business. Intergenerational authority, which refers to a senior generation that exercises unquestioned authority and sets the rules, is negatively related to the presence of a shared vision. Surprisingly, a third dimension of family climate, cognitive cohesion, which includes shared values in the family, had no relationship with the degree to which there was a shared vision for the family business. The implications for family business owners is that they would be wise to spend as much time on fostering a positive family climate characterized by open communication as they do on creating and executing a successful business strategy if their goal is to pass the business from one generation of family owners to the next.